IMPLEMENTASI STRATEGI PEMASARAN MEDIA SOSIAL INSTAGRAM TERHADAP PENINGKATAN PENJUALAN TOKO BAJUTTA - Fadillah, Ade Nurul; Ramlan, Pratiwi; Saleh, Wahyuni (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
This study aims to investigate the impact of implementing social media marketing strategies on increasing sales, using quantitative methods. With the development of social media, companies are increasingly using it as a tool to increase visibility and customer engagement. However, the effectiveness of social media marketing strategies in increasing sales is not fully understood. Therefore, this study takes a quantitative approach to measure the impact of social media marketing strategies on sales more objectively. Data were collected by observation, questionnaires, literature studies and interviews. The population was taken from the number of followers of the Toko Bajutta Instagram account, which was 1,017 followers and a sample of 91 people was taken using the Random Sampling sampling technique. Data analysis was carried out using appropriate statistical methods to identify the relationship between the implementation of social media marketing strategies and increased sales. The results of this study are expected to provide a deeper understanding of the role of social media in improving the company's sales performance.